Empowerment: Doctor vs Nurses - Akter, Silvia (Asian Business Review, 2012)
This paper aims to see the levels of empowerment exist in the private hospital in Dhaka city, considering the case of doctors and nurses. A small sample of 40 respondents from the two private hospitals was chosen randomly. The theories of empowerment are discussed and the results are analyzed in respect to the theories which shows that doctors are more empowered than the nurses.